A CASE STUDY OF LYMPHOCYSTIS VIRUS DISEASE IN FARMED GIANT SNAKEHEAD (Channa striata) IN MANDIANGIN, SOUTH KALIMANTAN - Bambang Setyo Sihananto; Hessy Novita; Christina Wianty; Angela Mariana Lusiastuti (Indonesian Aquaculture Journal, 2019)
Lymphocystis virus has been implicated as the cause of severe infection, mortality, and economic loss in farmed giant snakehead (Channa striata) or gabus fish in Mandiangin South Kalimantan. In Kalimantan, the fish is locally known as Haruan fish and considered to have health-related benefits to human due to its high albumin content. This study aimed to determine the LCDV in gabus fish through histopathological and PCR investigation. Infected LCDV fish have a cluster of warts growths in the skin or fin of a walleye. Infected fishes with an average of total length of 15 cm and weight of 150 g were collected from local net cages and earthen ponds. They were transferred into a laboratory, anesthetized, and then subsequently killed by organ dissection. The infected fish tumors were aseptically cut out for histological study and PCR detection. Primer used was forward GII F: 5 ‘TGG GAT TCC AAY GGT CAA TTA-3’ with target band of 468 bp (for genotype-IIi LCDV) and primer reverse R: 5’TTA GAT TAT TGG GCA GCG TT-3' with target band of 250 bp (for genotype-II LCDV) and GIII F: 5' AGG AAA TAA CCG CAG TA GAA TGCA. Lymphocytosis in infected fish showed multifocal to diffuse white, round, firm, papilloma or tumor-like nodules on the skin of the body, fins, eyes, and mouth. The hypertrophied cell was surrounded by a thick smooth hyaline capsule. Stress condition caused by high population density, nutrition deficiencies, decreased dissolved oxygen, suboptimal water quality, and handling may increase the appearance of LCDV symptoms. The result of the present study revealed that histopathology and PCR could be used to diagnose LCDV infection.